SEEDS GERMINATION OF RHIPSALIS IN DIFFERENT SUBSTRATES - LONE, Alessandro Borini; MOLO, Cecília Ximena; TAKAHASHI, Lúcia Sadayo Assari; UNEMOTO, Lílian Keiko (Scientia Agraria, 2009)
The work had as objective to evaluate different substrates in germination of Rhipsalis floccosa and Rhipsalis pilocarpa seeds. The tested substrates were: filter paper, sand of medium granulation, charred peel of rice, powder of coconut fiber and vermiculite, conditioned in transparent plastic boxes (gerbox). The germination test was accomplished in germinator with constant temperature of 25oC. The design was complete randomized with four replications for each treatment for each one of the species. Were appraised: germination percentage, speed germination index, and medium time of germination. Was verified larger percentage in the substrates paper, sand and charred peel of rice for both species. The smallest values for medium time of germination were observed in sand and charred peel of rice for R. floccosa and in powder of coconut fiber and charred peel of rice for R. pilocarpa. Was concluded that the best substrates for the germination of R. floccosa were sand and charred peel of rice and for germination of R. pilocarpa the best substrate was charred peel of rice.